2017
DOI: 10.1111/anae.14178
|View full text |Cite
|
Sign up to set email alerts
|

Regional nerve blockade for early analgesic management of elderly patients with hip fracture – a narrative review

Abstract: Elderly patients with hip fracture experience high morbidity and mortality, and are often undertreated for pain. Acute pain management in the elderly is challenging, with physiological frailty, medical comorbidities and cognitive impairment commonly compounding pain assessment and treatment. Guidelines outlining current best practice for acute pain management in the elderly now exist, but evidence suggests that practice remains variable and there continues to be scope for improvement. We conducted a narrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 108 publications
(138 reference statements)
1
94
0
2
Order By: Relevance
“…The effect of pre‐operative FNB on pain scores and use of rescue medicine has been investigated in other recent reviews, suggesting a decrease in pain scores and the use of rescue analgesics and a reduction in parenteral opiate use . Our review differs in the selection of FNB as we decided to investigate only FNB instead of mixing FNB, 3‐in‐1 femoral nerve block, fascia iliaca compartment block and other variants .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of pre‐operative FNB on pain scores and use of rescue medicine has been investigated in other recent reviews, suggesting a decrease in pain scores and the use of rescue analgesics and a reduction in parenteral opiate use . Our review differs in the selection of FNB as we decided to investigate only FNB instead of mixing FNB, 3‐in‐1 femoral nerve block, fascia iliaca compartment block and other variants .…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review investigating cognitive impairment following nerve block found moderate evidence that nerve blocks may contribute to reduce incidence of delirium, where as a recent systematic review did not find a difference in the incidence of acute confusional state. The narrative review included eight articles with a total of 666 patients, but pooled the results from different nerve blocks as FNB, 3 in 1 femoral nerve block and fascia iliaca block.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, multimodal drug therapy utilizes a variety of nonopioid analgesic medications in order to minimize dosage and prevent adverse effects from opioids while maximizing analgesic benefit [81]. A 2018 review showed that comprehensive pain protocols for elderly hip fracture patients are required, with fascia iliaca blocks as a local anesthesia method of choice [126]. Ultrasound-guided regional anesthesia/analgesia is an important part of anesthesia practice in the elderly population, the growth of which will continue to outpace that of the younger population due to improvements in lifespan worldwide [127].…”
Section: Perioperative Analgesiamentioning
confidence: 99%